INTERNSHIP PROGRAM FOR NOVICE TRANSLATOR: AN ANALYSIS ON TRANSLATION QUALITY - Fadhila, Aura; Fatkurochman, Henri (ELTIN Journal, 2024)
Novice translators often face various challenges in understanding and translating texts from one language to another. This study aimed at describing the development of translation quality of a novice translator’s work after joining internship program. Using a descriptive qualitative method, the data source was the translation result of the English text into Indonesian. This translation was produced by a novice translator during a three-month internship program. Documentary study was employed to collect the data. To analyze the data, it was used text and content analysis technique. Afterwards, the data are categorized based on Larson's theory (1997). The research result showed that the translation conducted by a novice translator was in better development in the quality and achieved acceptability on the target language (Indonesian).